Evolution and detection of Fusarium oxysporum f. sp. cepae in onion in South Africa - Southwood, Michael J. (Stellenbosch : Stellenbosch University, 2010)
Thesis (PhDAgric (Plant Pathology))--Stellenbosch University, 2010.